Relationship Between Self Esteem and Cheating Behavior of Junior High School Student - Almatin, Fauziah; Zikra, Zikra (Universitas Negeri Padang, 2023)
The background of this research is because there are still many cheating behaviors carried out by students at school. Both when completing assignments given by the teacher and during exams. One of the factors that cause cheating behavior is self-esteem. The objectives of this study are: (1) to analyze students' self-esteem; (2) to analyze students cheating behavior; (3) to examine the relationship between self-esteem and students' cheating behavior. This research uses a quantitative method with descriptive and correlational research types. The sample in this study was SMPN 35 Padang students for the 2022/2023 school year, a total of 158 students who were selected using s purposive sampling technique. The instrument used in this study is the instrument of self-esteem and cheating behavior using the Skala model Likert. The data analysis technique used was descriptive analysis and person product moment correlation analysis with the help of SPSS version 20.0 for windows. The research findings show that: (1) student self-esteem is generally in the moderate category with a percentage of 85,44 %, which means that many of the students in the sample have moderate self-esteem; (2) based on the results of the study explained that students cheating behavior were generally in the moderate category with a percentage of 34,18%, which means that some studens still practice cheating behavior; (3) there is a significant relationship between self-esteem and students cheating behavior with a correlation coefficient of -.456 at a significance level of 0.000. This means that the lower the self-esteem, the higher the student’s cheating behavior or vice versa. Based on the research results obtained, it is hoped that counseling teachers can play an active role in preventing and overcoming cheating behavior and helping students increase their self-esteem by providing assistance in the form of services related to self-esteem and cheating behavior. The services provided are information services, content mastery services, individual counseling, and group guidance regarding self-esteem and cheating behavior.